Mismatch, sorting and wage dynamics - Jeremy Lise; Costas Meghir; Jean-Marc Robin (Institute for Fiscal Studies (IFS), 2013)
We develop an empirical search-matching model which is suitable for analysing the wage, employment and welfare impact of regulation in a labour market with heterogeneous workers and jobs. To achieve this we develop an equilirium model of wage determination and employment which extends the current literature on equilibrium wage determination with matching and provides a bridge between some of the most prominent macro models and microeconometric research. The model incorporates productivity shocks, long-term contracts, on-the-job search and counter-offers. Importantly, the model allows for the possibility of assortative matching between workers and jobs due to complementarities between worker and job characteristics. We use the model to estimate the potential gain from optimal regulation and we consider the potential gains and redistributive impacts from optimal unemployment insurance policy. The model is estimated on the NLSY using the method of moments.
Keywords: 330; sorting; mismatch; search-matching; wage dynamics